Flipping the Classroom: An Evaluation of Teaching and Learning Strategies in the Operating Room. (June 2022) - Johnson, Jared; Misch, Emily; Chung, Michael T.; Hotaling, Jeffrey; Folbe, Adam; Svider, Peter F.; Cabrera-Muffly, Cristina; Johnson, Andrew P.
Objectives: With increasing restraints on resident's experiences in the operating room, with causes ranging from decreased time available to increasing operating room costs, focus has been placed on how to improve resident's education. The objectives of our study are to (1) determine barriers in education in the operating room, (2) identify effective learning and teaching strategies for residents in the operating room with a focus on the tonsillectomy procedure. Methods: An online survey was sent to all otolaryngology residents and residency programs for which contact information was available from January 2016 to March 2016 with 139 respondents. The 12-question survey focused on information regarding limitations to learning how to perform tonsillectomies as well as difficulties with teaching the same procedure. Resident responses were separated based on PGY level, and analysis was performed using t -tests and Chi squared analysis. Results: Common themes emerged from responses for both teaching and learning how to perform tonsillectomies. A significant limitation in learning the procedure was lack of visualization during the surgery (57% learning vs 60% teaching). For both learners and teachers, the monopolar cautery instrument was found to be the most preferred instrument to use during tonsillectomy (80% each). The majority of resident respondents (93%) felt that an instructional video would be beneficial for both learning and teaching the procedure. Conclusions: Significant limitations for learning and teaching in the operating room were identified for performing tonsillectomies. Future endeavors will focus on resolving these limitations to improve surgical education. Evidence level: Level IV.